2014
DOI: 10.1371/journal.pone.0111418
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor 21 Is Not Required for the Reductions in Circulating Insulin-Like Growth Factor-1 or Global Cell Proliferation Rates in Response to Moderate Calorie Restriction in Adult Mice

Abstract: Calorie restriction (CR) delays aging and extends lifespan in numerous organisms, including mice. Down-regulation of the somatotropic axis, including a reduction in insulin-like growth factor-1 (IGF-1), likely plays an important role in CR-induced lifespan extension, possibly by reducing cell proliferation rates, thereby delaying replicative senescence and inhibiting tumor promotion. Accordingly, elucidating the mechanism(s) by which IGF-1 is reduced in response to CR holds therapeutic potential in the fight a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 61 publications
1
14
0
Order By: Relevance
“…Finally and importantly, only HFLP produced a significant change in liver Fgf21 mRNA expression and circulating FGF21 protein. These data highlight the differences between protein restriction and dietary restriction, particularly the selective increase of FGF21 ( Laeger et al, 2014a ; Solon-Biet et al, 2016 ; Thompson et al, 2014 ; Zhang et al, 2012 ).…”
Section: Discussionmentioning
confidence: 79%
“…Finally and importantly, only HFLP produced a significant change in liver Fgf21 mRNA expression and circulating FGF21 protein. These data highlight the differences between protein restriction and dietary restriction, particularly the selective increase of FGF21 ( Laeger et al, 2014a ; Solon-Biet et al, 2016 ; Thompson et al, 2014 ; Zhang et al, 2012 ).…”
Section: Discussionmentioning
confidence: 79%
“…In ApoE-deficient mice subjected to long-term caloric restriction, FGF21 decreased when compared with controls during the first 25 weeks of caloric restriction and then increased over the controls from 30 to 64 weeks [ 33 ]. Plasma FGF21 has also been reported to be upregulated in mice subjected to caloric restriction for 4–6.5 weeks [ 34 ]. In our study, plasma FGF21 concentrations were consistently lower at the three sampling times in rats fed hypocaloric diets than in rats fed normal and high calories.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, plasma FGF21 concentrations were consistently lower at the three sampling times in rats fed hypocaloric diets than in rats fed normal and high calories. Several factors may explain the discrepancy with studies that have found an increase in FGF21 after calorie restriction: (a) Previous studies have been conducted in mice which may behave differently to rats, (b) time of sampling may be important because FGF21 has been shown to be affected by circadian rhythm [ 35 ] and in some studies, e.g., Thompson et al [ 34 ], mice were sampled at night time, while in our study the rats were sampled in the morning, between 9.00 and 11.00 h. In our opinion, the most important factor to explain the FGF21 concentrations detected in rats fed LC is the fact that these rats were subjected to calorie restriction but not to protein restriction, which seems the main trigger of FGF21 elevation [ 32 ]. In fact, the LC diet used in the present study has a high protein (52%) content.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, this phenomenon was in part attributed to the ability of FGF21 to inhibit growth hormone (GH) signalling , and its effects on growth plate chondrocytes . Nonetheless, growth/bone phenotypes in FGF21 null mice were seen only under caloric restriction and not in animals fed ad libitum , and the existence of an FGF21–IGF1–GH axis in mice was recently questioned . It is therefore possible that the above‐mentioned exaggerated growth and bone phenotypes are due to the differences in whole‐body energy balance between gain/loss of function and naĂŻve animals rather than resulting from direct action of FGF21.…”
Section: Adverse Effects Of Fgf21: Torpor Reproduction and Bone Turnmentioning
confidence: 99%